(untitled) (Società e diritti, 2022)
The work aims to demonstrate the constitutional illegitimacy of Articles 2 and 4 of the bill n. 1785 laying rules about gender quotas in the italian Corte costituzionale and Consiglio Superiore della Magistratura.